Crack growth of explosive welding zirconium-steel bimetal subjected to cyclic bending - D. Rozumek; Z. Marciniak (Fracture and Structural Integrity)
The paper presents the fatigue test results including the cracks growth in the composite zirconium-steel subjected to oscillatory bending. Specimens of square cross-section without melted layer and with a melted layer were tested. In the specimens the net ratio of thickness of steel to zirconium layers was h1 : h2 = 2.5 : 1. It was observed that a higher fraction of the intermetallic inclusions near the interface increase the fatigue life. Two different interaction mechanisms between a crack and interface were observed.